"Giler" or "Gile": Use of Slang Words as Intensifiers: ("Giler" atau "Gile": Slanga Kata Penguat) (Jurnal Bahasa, 2018)
This article focuses on the use of the slang word "giler" or "gile" (lit.: mad, crazy) which has become common usage as an intensifier. The occurrence of this word, whether before or after adjectives, and its intensifying function in adjectival phrases, is examined. Data was collected through random interviews and online questionnaires. The study reveals that these slang words are often used as intensifiers, and are commonly used both in spoken language and informal written communication by the public, regardless of age, gender, educational background, profession or ethnicity.Keywords: intensifiers, slang, language and linguistics, language variation